Formação policial : contribuições pedagógico-filosóficas - Detoni, Maurício Paraboni (2013)
The professional training police in Brazil have been precarious and, moreover, marked by a predominance of authoritarian and detached from society. For this reason, the challenge to qualify the police to allow her approach with the citizens, as well as the intention of providing some educational grants for the development of a public safety service quality are objectives of this dissertation. It is an arduous task, but presents numerous alternatives. This study presents the proposition of police training be developed critical-hermeneutic perspective, rooted especially in Hans-Georg Gadamer. It is considered that such an approach may be an important mechanism of change in the way the police action in dealing with people and the community. Therefore, at first, are brought historical aspects of the constitution of institutions, showing the roots that gave rise to the training model developed in different phases, showing especially as the internal struggles and the period of military rule have left indelible marks in regard to the training of military police. In the second stage of the work, we analyze the curricula of Training Courses Soldiers of the last thirty-one years Military Police verifying training structures centered on the use of force, despite the daily police be directed to the maintenance actions peace. In the last part of the research, it is proposed to change the current scenario for the formation of valued professional with appropriate academic training, breaking with the idea of instrumental education, aiming at the formation of an ethical subject, savvy, critical and autonomous through a space that fosters understanding of values such as tolerance, cooperation, solidarity, humility, respect and justice, followed by period of specific technical training center for this. It is believed that in this way you can promote yourself to a more qualified training of police, contribute to their dignity and, in particular, make the police action an activity primarily focused on conflict resolution and the promotion of peace